Cost effectiveness and data-yield of biodiversity surveys - Bisevac, L.; Majer, Jonathan (2002)
The most common approach to general biological surveys is based on various measures of plant communities in the investigated area. Fauna are not usually considered, and if animals are included the emphasis is generally on the more "charismatic" vertebrates. Invertebrates are ideally suited for conveying information about the environmental status of an area. This paper makes a comparison of the logistics of performing plant, vertebrate and invertebrate samples in a biological survey. Evidence is presented which indicates that the inclusion of invertebrates in surveys can contribute to data on physical factors, as well as on plant and vertebrate communities. Some invertebrate taxa are richer in species than the corresponding vertebrate fauna. In terms of trends in species richness across sites, and also in terms of changes in community composition, certain invertebrates portray a better interpretation of changes in habitat than do the vertebrates. It is suggested that invertebrates can provide a cost-effective means of generating information on the environmental status of an area.